Temporomandibular disorder pain improvement with acupuncture: preliminary longitudinal descriptive study - Bruna Angeleli Bueno de Camargo; Cássia Maria Grillo; Maria da Luz Rosário de Sousa (Revista Dor)
BACKGROUND AND OBJECTIVES:Acupuncture is a therapeutic method widely used to manage pain. Temporomandibular disorders have symptoms such as facial pain, pain in temporomandibular region and in masticatory muscles. This study aimed at describing the results obtained in temporomandibular disorder pain intensity improvement in patients treated in a public service with a minimum number of three acupuncture sessions.METHODS:This is a descriptive study with patients with temporomandibular disorders treated in the Dentistry Specialties Center I of the city of Piracicaba (SP) in the period from September 2010 to October 2011. Sample was made up of 31 patients of both genders, aged between 14 and 68 years. Pain was measured by the visual analog scale (VAS), called initial VAS (pre-treatment) and final VAS (post-treatment), respectively in the beginning and end of the acupuncture session. Each patient was submitted to three 20-minute sessions, once a week.RESULTS:Pain was absent (VAS=0) in 67.7% of patients who had pain intensity improvement with iVAS in the first session higher (6.10±2.64) than fVAS in the third session (1.16±1.98).CONCLUSION:With a minimum of three weekly acupuncture sessions it was possible to control temporomandibular disorder pain regardless of the level of initial pain. Its use could contribute to enhance the treatment of such patients in the public service for being a low cost and easy to apply therapy.